2006
DOI: 10.1016/j.chembiol.2005.11.012
|View full text |Cite
|
Sign up to set email alerts
|

AEG3482 Is an Antiapoptotic Compound that Inhibits Jun Kinase Activity and Cell Death through Induced Expression of Heat Shock Protein 70

Abstract: We describe a group of small-molecule inhibitors of Jun kinase (JNK)-dependent apoptosis. AEG3482, the parental compound, was identified in a screening effort designed to detect compounds that reduce apoptosis of neonatal sympathetic neurons after NGF withdrawal. We show that AEG3482 blocks apoptosis induced by the p75 neurotrophin receptor (p75NTR) or its cytosolic interactor, NRAGE, and demonstrate that AEG3482 blocks proapoptotic JNK activity. We show that AEG3482 induces production of heat shock protein 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 57 publications
0
37
0
Order By: Relevance
“…Apoptosis by Hsp70 shRNA was also induced in the absence of A/-N (King, 2007). Hsp70 is pluripotent, protecting cells against apoptosis at multiple levels, including JNK activity suppression (Salehi et al, 2006;Bienemann et al, 2008), Bax translocation (Stankiewicz et al, 2005), cyt c release (Creagh et al, 2000), apoptosome assembly (Beere et al, 2000;Saleh et al, 2000), and caspase activation (Mosser et al, 1997). JNK activation remained intact in Q97-expressing neurons, eliminating its suppression by Hsp70 as the reason for apoptosis inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis by Hsp70 shRNA was also induced in the absence of A/-N (King, 2007). Hsp70 is pluripotent, protecting cells against apoptosis at multiple levels, including JNK activity suppression (Salehi et al, 2006;Bienemann et al, 2008), Bax translocation (Stankiewicz et al, 2005), cyt c release (Creagh et al, 2000), apoptosome assembly (Beere et al, 2000;Saleh et al, 2000), and caspase activation (Mosser et al, 1997). JNK activation remained intact in Q97-expressing neurons, eliminating its suppression by Hsp70 as the reason for apoptosis inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…EGF (human, recombinant) and sorafenib were from Funakoshi (Tokyo, Japan) and American Chemicals Custom (San Diego, CA, USA), respectively. GA and 17-AAG were used at concentrations reported previously (Sano, 2001;Salehi et al, 2006;Clark et al, 2009). The concentrations of other reagents were also the same as those in previous reports (Taniguchi et al, 2007;Kurosawa et al, 2009;Tada et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…(ROS)-related stimuli and/or stress specifically at greater concentrations (from 10 nM to 10 μM), and showing neuroprotective effects at lower concentrations (nM order) (Sano, 2001;Lu et al, 2002Lu et al, , 2009Kim et al, 2003;Salehi et al, 2006;Clark et al, 2009). However, the precise mechanism(s) for the dual effects of Hsp90 inhibition on cell fate has not been established, and the effects of Hsp90 inhibitors on orthovanadate, Na 3 VO 4 , -induced cytotoxicity have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…7 shows that expression of full-length p75NTR or the p75ICD rescued the growth-arrest phenotype, but full-length p75NTR that was cleavage resistant did not. We and others have shown that massive overexpression of full-length p75NTR or the p75ICD induces caspase cleavage and cell death (Bhakar et al, 2003;Kenchappa et al, 2006;Salehi et al, 2006), but supplementary material Fig. S4 shows that the modest overexpression of p75NTR or p75ICD used in this paradigm has no effect on caspase activation.…”
Section: P75ntr Cleavage Promotes Ngf-induced Growth Arrest Of Pc12 Cmentioning
confidence: 99%